The Impact of Land Price Movements on the Properties in Croatia (Journal of Social Economics Research, 2020)
The Mediterranean countries of the European Union record diversions in real estate along the coast. Based on the hypothesis that land prices are playing a significant role in increasing housing prices, the goal of our research was to determine to what extent that factor is important in Croatia. The reason for price unsteadiness is most often examined through main macroeconomic aspects but very few researches are using land prices as the main assumption of this problem. The study is carried out using Davis and Heathcote (2005) for determining factors of home value. By observing the period from 2002 to 2017 and from the given results we were able to deliver prediction for future market movements until 2025 using the Double exponential smoothing model. The analysis showed that there is a positive correlation between financial crisis and fall of land price index in all parts of Croatia except the coastal region as research proposed initially. It is shown that real estate prices will continue to grow, but the index of land prices will not follow this growth in parallel. Rather other factors like cost of building will have bigger share in the overall price. The outcome provides an important opportunity to advance the understanding of housing market movements in Croatia by regions and might serve as guidance in future policy creation.